Analysis of data from a free-listing study of menus by different income-level populations - Libertino, Luciano Martin (2012)
Free listing can help understand how a domain is perceived across a group of people by examining the average psychological saliency of items, in this case, menus elicited by a population. The objectives of the present work were: (a) compare different indexes used to analyze the saliency of items listed by individuals in a free-listing exercise, (b) test if time distance can be an improvement over rank distance in associating items mentioned by subjects, and (c) apply the above indexes and associations to gain insight in the menus listed by different income-level populations in Argentina. In the present study we surveyed a total of 200 women from low and medium/high-income levels who were asked to list all the menus they knew registering the mention order and time to mention. Smith's saliency index and cognitive salience index (CSI), previously not applied in the food science literature, proved useful in selecting the core menus listed by a population. The hypothesis that time distance would be a more adequate measure of the association of items in a list than order of mention was not sustained in the present study. Cluster analysis was also found useful in analyzing how menus were grouped by different income levels using a free-listing procedure. ANOVA on the CSI values showed a significant menu × income-level interaction, thus indicating that saliency was not the same for listed menus across income levels.